(untitled) (Contemporary Journal of Social Science Review, 2025)
The Prophet Muhammad (peace be upon him) provided comprehensive guidance to his Ummah in all aspects of life. Among his core teachings is the principle of controlling one’s tongue—refraining from unnecessary speech and using words only for good. He emphasized that a believer should avoid speech that leads to harm, conflict, or mischief, and instead speak only when it serves a positive and meaningful purpose. The Prophet’s own example reflects this teaching, as he would often remain silent and only speak when necessary, with wisdom and benefit. His Companions, trained under his guidance, also adopted this practice. They would generally remain silent unless there was something beneficial to say, and they carefully avoided words that could lead to fitnah (discord). In parallel, the Prophet (peace be upon him) strongly encouraged the frequent remembrance of Allah (dhikr), considering it a vital part of spiritual life. He taught that the one who remembers Allah and the one who does not are like the living and the dead. The Qur’an also highlights constant remembrance of Allah as one of the key traits of the people of understanding. In today’s society, many people engage in excessive and thoughtless speech, often leading to unnecessary conflict, misunderstanding, and social unrest. One of the root causes of this issue is a lack of awareness or understanding of Islamic teachings related to the responsible use of speech and the importance of dhikr. This research explores the Qur’anic and Prophetic guidance regarding speech, silence, and remembrance of Allah. It aims to highlight the spiritual and social impact of these teachings and encourages a shift towards more conscious, purposeful, and spiritually rooted communication. The study aspires to contribute to fostering a more peaceful, disciplined, and ethically aware society.